Stemness Maintenance Properties in Human Oral Stem Cells after Long-Term Passage. (2nd April 2017) - Diomede, Francesca; Rajan, Thangavelu Soundara; Gatta, Valentina; D'Aurora, Marco; Merciaro, Ilaria; Marchisio, Marco; Muttini, Aurelio; Caputi, Sergio; Bramanti, Placido; Mazzon, Emanuela; Trubiani, Oriana
Abstract : Background . Neural crest-derived mesenchymal stem cells (MSCs) from human oral tissues possess immunomodulatory and regenerative properties and are emerging as a potential therapeutic tool to treat diverse diseases, such as multiple sclerosis, myocardial infarction, and connective tissue damages. In addition to cell-surface antigens, dental MSCs express embryonic stem cell markers as neural crest cells originate from the ectoderm layer. In vitro passages may eventually modify these embryonic marker expressions and other stemness properties, including proliferation. In the present study, we have investigated the expression of proteins involved in cell proliferation/senescence and embryonic stem cell markers during early (passage 2) and late passages (passage 15) in MSCs obtained from human gingiva, periodontal, and dental pulp tissues. Methods . Cell proliferation assay, beta galactosidase staining, immunocytochemistry, and real-time PCR techniques were applied. Results . Cell proliferation assay showed no difference between early and late passages while senescence markers p16 and p21 were considerably increased in late passage. Embryonic stem cell markers including SKIL, MEIS1, and JARID2 were differentially modulated between P2 and P15 cells. Discussion . Our results suggest that the presence of embryonic and proliferation markers even in late passage may potentially endorse the application of dental-derived MSCs in stem cell therapy-based clinical trials.